Computer modeling of optimal portfolio construction - Данилевич, Сергей Борисович; Дьячкова, Ольга Владимировна (Eastern-European Journal of Enterprise Technologies, 2012)
The methods and practical recommendations for automation of the optimal portfolios formation processes via MS Excel are presented